(untitled) (Advancements in Homeopathic Research, 2025)
NAFLD is an important cause of liver disease in India. During the past century, dramatic modifications in lifestyle have radically changed the health priorities in most areas of the world, owing to a growing incidence of non-communicable disease. Fatty liver has earlier often been related with excessive alcohol consumption. During the past 20 years, the interest in fatty liver occurring in non-drinkers i.e. non-alcoholic fatty liver disease (NAFLD) has raised quickly. Methods A prospective experimental study design without control group.Patients will be collected from the In-patient and Out-patient Departments, Peripheral Centres, Rural Health Camps and Medical Camps conducted by Vinayaka Mission’s Homoeopathic Medical College and Hospital Result This study provides evidence to say that, there is significant reduction in the Non-alcoholic fatty liver disease after giving homoeopathic constitutional medicine